2010
DOI: 10.1103/physreva.81.045602
|View full text |Cite
|
Sign up to set email alerts
|

Double occupancies in confined attractive fermions on optical lattices

Abstract: We perform a numerical study of a one-dimensional Fermion-Hubbard model in harmonic traps within the Thomas-Fermi approximation based on the exact Bethe-ansatz solution. The ρ − U/t phase diagram is shown for the systems of attractive interactions (ρ is the characteristic density and U/t the interaction strength scaled in units of the hopping parameter.). We study the double occupancy, the local central density and their derivatives. Their roles are discussed in details in detecting the composite phases induce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Comparisons between hightemperature series expansions, dynamical mean-field theory, and experiment were also useful in using double occupancy to measure the temperature of fermions in optical lattices [25]. More recent calculations have shown that the fermion core compressibility can be very useful in one-dimensional optical lattices as well [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons between hightemperature series expansions, dynamical mean-field theory, and experiment were also useful in using double occupancy to measure the temperature of fermions in optical lattices [25]. More recent calculations have shown that the fermion core compressibility can be very useful in one-dimensional optical lattices as well [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Parallel to the experimental progress of manipulating fermions in optical lattices, recently there have been theoretical studies on the role of an external harmonic potential and its effect on compressibility and double occupancies [11][12][13][14][15][16]. The underlying harmonic trapping potential present in all cold-gas experiments causes density to vary across the lattice.…”
Section: Introductionmentioning
confidence: 99%
“…At zero temperature and high temperatures, our work is complementary to some of the work presented in Refs. [11][12][13][14][15][16][17]. However, we go beyond these studies by systematically extending zero-temperature calculations to any finite temperature.…”
Section: Introductionmentioning
confidence: 99%